2020
DOI: 10.26710/sbsee.v2i2.1617
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Liquidity Considering Role of Market Competition; Evidence from Pakistan’s Banking Sector

Abstract: Current study empirically analyzes bank specific factors and macroeconomic factors that determine the liquidity reserves of banks functioning in Pakistan. To highlight the association, current study performed random effects estimates on a data set of 20 banks from 2006 to 2016.  Bank specific factors include bank size, capital and credit Risk. GDP and Inflation are the macroeconomic factors that were considered. Market competition has been measured through HHI. Based on panel data analysis, current study sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…During the study period, the research found no impact of inflation, loan growth, interest rate margin, and nonperforming loans on Ethiopian banks' liquidity. Rafique et al (2020) conducted a study on Pakistani banks from 2006 through 2016 and identified the determinants of macroeconomic and bank-specific factors over banks' liquidity reserve. Through the panel data method, the study implemented random-effects estimates over 20 banks dataset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…During the study period, the research found no impact of inflation, loan growth, interest rate margin, and nonperforming loans on Ethiopian banks' liquidity. Rafique et al (2020) conducted a study on Pakistani banks from 2006 through 2016 and identified the determinants of macroeconomic and bank-specific factors over banks' liquidity reserve. Through the panel data method, the study implemented random-effects estimates over 20 banks dataset.…”
Section: Literature Reviewmentioning
confidence: 99%